Penentuan Harga Pelayanan Publik Pendekatan Keadilan Dan Efisiensi Dalam Pelayanan Pemerintah Daerah - Agnes Widyastuti; Marsya Yunistiani; Margaretha Grace Christiani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the determination of public service tariffs at the local government level. The method used is a qualitative approach with data collection techniques in the form of literature studies, observations, and policy documentation. The results of the study indicate that tariff determination is not yet fully transparent and participatory. A fair, efficient, and community-involved tariff policy is needed to increase the legitimacy and sustainability of public services.